2018
DOI: 10.1007/s11332-017-0422-1
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and lipid profile of regular recreational table tennis participants: a cross-sectional study of older adult men

Abstract: The aim of the present study was to investigate the effects of regular participation in recreational table tennis training on bone health, body composition and lipid profile of elderly men. 20 regular recreational table tennis players (11.6 ± 3.6 years of experience) and 20 sedentary older adults (age, mass and sex matched of 65-75 years) participated in the study. Serum triglycerides, total cholesterol, HDL-cholesterol, and LDL-cholesterol concentrations were determined after 12 h fasting. Body composition wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…Foot fatigue was defined as a reduced ability of, in this case, the foot muscles to develop the required force during continued contractile activity [20]. The excessive pronation increases the risk of running-related injury, such as medial tibial stress syndrome, due to the accumulation of microtrauma arising from repetitive undue loading of tendons, muscles and bones [19,21,22].…”
Section: Dynamic Plantar Pressure Distributionmentioning
confidence: 99%
“…Foot fatigue was defined as a reduced ability of, in this case, the foot muscles to develop the required force during continued contractile activity [20]. The excessive pronation increases the risk of running-related injury, such as medial tibial stress syndrome, due to the accumulation of microtrauma arising from repetitive undue loading of tendons, muscles and bones [19,21,22].…”
Section: Dynamic Plantar Pressure Distributionmentioning
confidence: 99%
“…More specifically, previous studies reported low blood-lactate concentrations (<2.5 mmol·L −1 ) after a competitive table tennis game [ 19 ], suggesting that work–rest ratio is sufficiently balanced to avoid glycogen depletion and reaching the sensation of discomfort accompanying muscle fatigue [ 24 , 25 ]. Because of these particular physical demands, table tennis appears to contribute to maintaining a healthy body composition (i.e., appropriate amount of body fat, lean muscle mass, and bone health) among regular adult practitioners [ 26 ]. While there are no data available on children, it can be expected that regular table tennis practice twice a week constitutes an enjoyable activity that would contribute considerably to satisfying the recommended level of moderate to vigorous physical activity in children [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have highlighted the benefits of playing table tennis as a form of recreation and leisure, such as improving hand-eye coordination [ 1 ], improving balance, coordination, brain stimulation and development of cognitive functions [ 2 ], development of body build, and improving fat distribution [ 3 ]. Furthermore, as a sport practiced by professional players, table tennis is extremely demanding.…”
Section: Introductionmentioning
confidence: 99%